An investigation into rape myth acceptance between sexes in relation to gender roles of South African university students. - Dunseith, Olivia (My University, 2011)
Female rape myth acceptance has been studied for decades but to date very little is known about male rape myth acceptance and neither has been researched in a South African context. This study investigated four main areas around male and female rape myth acceptance, including: whether sex and an individual’s attitudes about traditional gender roles predicted rape myth acceptance, whether gender role identity moderated the relation between sex and rape myth acceptance, whether rape myth acceptance was affected by rape salience, and whether rape myth acceptance, traditional gender roles, and sex predicted the likelihood that participants would report rape if it were to happen to them. Men were found to hold higher male and female rape myth acceptance than women and overall, androgynous sex typed males and females were least likely to accept male and female rape myths. The current study found that the rape scenario depicting a male victim elicited higher female rape myth acceptance and that when a male rape victim was made salient, male participants evidenced higher male rape myth acceptance. Finally, men were found to be the least likely to report a rape if it were to happen to them especially if they accepted male rape myths and were more masculine in their sex type traits. Implications of these findings are discussed and directions for future research are explored.